Strategies for Utilizing Cold Storage Technology in Maintaining the Quality and Quality Standards of Horticultural Vegetables After Harvest (Case Study of CV. Family Garden Mart) - Ardi, Muhammad Syawaludhin; Bahari; Sadimantara, Fahria Nadiryati (International Journal of Technology and Education Research, 2025)
This study aims to determine how the strategy of utilizing cold storage technology in maintaining the quality and quality standards of post-harvest horticultural vegetables and to find out what quality standards and quality standards of horticultural vegetables are applied by the company. This research was conducted from January 2024 to April 2025. This research is a case study, with the owner of CV Family Garden Mart serving as the primary source of information required by the researcher. The data obtained were analyzed using qualitative descriptive analysis. The results of this study indicate that the treatment applied to vegetable products includes product inspection, weighing, packaging, determining the storage position in cold storage, setting the temperature, maintaining the cleanliness of the storage room, and implementing the FIFO (First In, First Out) system. The company uses cold storage with an area of 15.39 m² and a volume of 41.55 m³, and the storage temperature used is between 0-4°C, which can maintain the shelf life of vegetables for 2-3 weeks. Observations show that the company sets quality standards for each type of vegetable, namely red peppers (Quality II), yellow peppers (Quality I), broccoli (Quality I), potatoes (Quality II), tomatoes (Quality I), and carrots (Quality I). Based on the analysis of the relationship between technical parameters and vegetable quality, it was found that the technical aspects of storage and packaging have a strong relationship with the final quality of the product compared to other parameters